1987
DOI: 10.1063/1.339742
|View full text |Cite
|
Sign up to set email alerts
|

An i ns i t u study of dissolution and swelling behavior of poly-(methyl methacrylate) thin films in solvent/nonsolvent binary mixtures

Abstract: A single-element rotating-polarizer ellipsometer (psi-meter) was used for in situ characterization of the thermodynamic and kinetic behavior of poly-(methyl methacrylate), PMMA, thin films (1.2 μm) in solvent/nonsolvent binary mixtures of methyl ethyl ketone/isopropanol (MEK/IPA) and methyl isobutyl ketone/methanol (MIBK/MeOH). Thermodynamic effects were inferred from equilibrium behavior by the degree of swelling and polymer-solvent solubility. A sharp transition between complete solubility and almost total i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 5 publications
4
28
0
Order By: Relevance
“…Previous work has shown that blends of good solvents and non-solvents can readily swell polymer fi lms, [ 85,86 ] We consider two cases when designing a blended fullerene deposition solvent: polymers that are insoluble in 2-CP (e.g., PSDTTT), and polymers that are soluble in 2-CP (e.g., PTB7). When 2-CP does not dissolve the polymer underlayer, swelling must be increased (i.e., χ must be decreased) by blending 2-CP with a good solvent for the polymer.…”
Section: Creating High Performance Bhj Opvs With the Sqp Co-solvent Amentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that blends of good solvents and non-solvents can readily swell polymer fi lms, [ 85,86 ] We consider two cases when designing a blended fullerene deposition solvent: polymers that are insoluble in 2-CP (e.g., PSDTTT), and polymers that are soluble in 2-CP (e.g., PTB7). When 2-CP does not dissolve the polymer underlayer, swelling must be increased (i.e., χ must be decreased) by blending 2-CP with a good solvent for the polymer.…”
Section: Creating High Performance Bhj Opvs With the Sqp Co-solvent Amentioning
confidence: 99%
“…This is why we chose IPA as our typical non-solvent, since alcohols readily wet most conjugated polymers as well as maintain or even enhance their swelling. [85][86][87][88][89] …”
Section: Creating High Performance Bhj Opvs With the Sqp Co-solvent Amentioning
confidence: 99%
“…It can also provide quantitative information on the thickness of the transition layer between the dissolving polymer and liquid solvent. Rodriguez and co-workers [15,16,18,30,31] studied polymer dissolution for microlithography applications extensively. The basic apparatus is shown in Fig.…”
Section: Interferometrymentioning
confidence: 99%
“…Mixed solvents were also studied by Manjkow et al [31]. Solvent/non-solvent binary mixtures of MEK and isopropanol (MEK/IpOH) and MIBK and methanol (MIBK/MeOH) were used.…”
Section: Effects Of Different Solvents and Additivesmentioning
confidence: 99%
“…The resolution and minimum achievable pitch is not limited by the e-beam size (<3 nm). Instead, they are determined by resist swelling [7], proximity effect that leads to an undercut profile, and capillary force during the drying of the rinse solution, here IPA. Cellosolve developer that has a lower contrast suffers more from proximity effect, leading to more pronounced resist line distortion and collapse.…”
mentioning
confidence: 99%